Application of the Maxillofacial Mini-plate Compact 1.0 in the Fracture Repair of 12 Cats/2 Dogs - von Werthern, C. J.; Bernasconi, C. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
This study reports the application of the AO/ASIF maxillofacial mini-plate system, Compact 1.0a (MF mini-plate 1.0), in the repair of fractures in 12 cats and two small sized dogs. The malleability of these titanium mini-plates allows them to be precisely contoured and positioned to fit onto the most advantages sites of the bone. Selftapping mini-screws provide an easy application and a time-saving osteosynthesis. Fractures of miniature bones too small for the regular AO/ASIF miniimplants can be repaired successfully with this MF mini-plate 1.0 implant set. The special indications reported were the repair of fractures of the angle of the mandible in cats, articular digital fractures in small dogs and the stabilization of small avulsion fractures in cats and dogs.This study shows the successful application of the titanium maxillofacial mini-plate, Compact 1.0, in 12 cats and two toy breed dogs. Miniature fractures, such as mandible or digit fractures, too small for the AO/ASIF mini-plate system are indications for these implants. The self-tapping screws of the maxillofacial system, Compact 1.0, with a core diameter of 0.7 mm, can be used as plate screws or interfragmentarily.
Keywords: Maxillofacial plate; mandibular fractures; cat; toy breed dog